The Role of Interpersonal Communication in Building Family Resilience - Fadyla Ayu Wardhany; A.A.A Bintang Kesuma Dewi; Deti Rizki Nabawiyati (International Conference on Psychology and Education (ICPE), 2023)
The purpose of this study was to determine the resilience of interpersonal communication in building a family. This article research uses the literature study method by looking for theoretical references that are relevant to the cases or problems found. From several literature studies on theoretical references that have been carried out, the results and conclusions are as follows: interpersonal communication can strengthen family function in facing challenges, there is a significant relationship between interpersonal communication in families and juvenile delinquency, interpersonal communication carried out by parents can affect opportunities increasing religious knowledge in children. The results of the study show that interpersonal communication can build family resilience but the level of communication between parents and children still tends to be low.